Paving the Way for Women with Asperger Syndrome - Hurlbutt, Karen (Journal of the American Academy of Special Education Professionals, 2007)
More information is becoming available about Asperger Syndrome (AS), especially regarding the educational needs of children. There is a lack of available information, however, regarding adults with AS, particularly women. Five women with AS participated in this qualitative research study over a two-year period. The purpose was to investigate and describe their perceptions of their experiences about being a woman on the autistic spectrum. Methods included conducting initial and follow-up interviews via telephone and email. It was determined that the women with AS perceived their interests when growing up as being atypical, struggled with the diagnosis process and with relationships with males, and experienced difficulty with employment. Recommendations to parents and professionals involved in working with girls/women with AS are provided. While more and more information is becoming available regarding Asperger Syndrome (AS) in general, and specifically regarding children with AS, there is not enough information available regarding adults with AS. Information about women with AS is even less scarce, although a few books have been written by these women to help parents, teachers, and professionals learn more about them (Grandin, 1986; Grandin, 1995; Grandin & Duffy, 2004; Holliday Willey, 1999; Miller, 2003; Williams, 1992). These authors are well-known in the autism community and are typically considered to be "successful" women. One of the best ways to learn more about the lives of women with AS, especially those who may not be considered "successful" by others (i.e., who have not published books or other written material), is to talk to these women and allow them the opportunity to share their stories and perceptions of their own lives. The purpose of this preliminary study was to provide an opportunity for women with AS to share their perceptions of their life experiences of being a woman with Asperger Syndrome.